Electrophoretic focusing on inverse electromigration dispersion gradient. The fundamental resolution equation and pressure-assisted performance enhancement - Malá, Zdena; Gebauer, Petr (Journal of chromatography. A, 2018)
Electrophoretic focusing on inverse electromigration dispersion (EMD) gradient is a new analytical technique based on a unique separation principle where weak non-amphoteric ionogenic species are focused, separated and transported to the detector by an EMD profile of suitable properties. The present work extends the theoretical description of this method by introducing the concept of resolution and deriving the fundamental equation expressing resolution as function of basic system parameters. The results indicate that at constant current operation, resolution is proportional to the square root of time. For variable current regimes (e.g. constant voltage), the time variable is replaced by the product of electric current and passed electric charge. Computer simulations for a model pair of substances support the validity of the presented theory and confirm the theoretical conclusion that resolution can be increased by allowing longer electromigration of the gradient in terms of time or passed charge. The experimental example shown comprises an anionic electrolyte system based on maleic acid and 2,6-lutidine, combined with ESI-MS detection and operated in the reverse mode due to strong electroosmotic flow and ESI suction. The practical implementation of the proposed methodology is done by application of negative pressure at the inlet vial, resulting in very substantial resolution enhancement and baseline separation of otherwise unresolved substances. The performance and high sensitivity of the developed technique is demonstrated on the example of simultaneous analysis of four sulfonamides and three dichlorophenols in waters with limits of detection on the 1 nM level.
Keywords: chlorfenoly; Chlorophenols; Sulfonamides; Focusing; elektrolyty; maleáty; elektroforéza kapilární; Water analysis; pitná voda; Maleates; Drinking Water; Capillary electrophoresis; limita detekce; Spectrometry, Mass, Electrospray Ionization; pyridiny; Pressure; Resolution; tlak; Pyridines; Limit of Detection; hmotnostní spektrometrie s elektrosprejovou ionizací; Electrophoresis, Capillary; sulfonamidy; Electrolytes